Hba1c Variability Has a Strong Relationship With Peripheral Sensory And Motor Neuropathy in Type-2 Diabetes Mellitus (Journal of Bio-Science, 2021)
Diabetic peripheral neuropathy (DPN) is one of the most common long-term microvascular complications of diabetes. This study was undertaken to investigate the association of HbA1c variability with diabetic peripheral neuropathy (sensory and motor) in patients with type-2 diabetes. In this study, a total of 150 type-2 diabetic patients were screened for DPN and undergone quarterly HbA1c measurements during the year preceding enrolment were recruited. DPN was confirmed in patients displaying both clinical manifestations of neuropathy and neurological abnormalities assessment. Among the recruited patients, 24% were found to have DPN (sensory and motor), and these patients also presented with a higher HbA1c as compared to the patients without DPN (p